Effect of perceptual-motor training on motor skills of girls with trainable Mental Retardation - Hasan Baghande; Davoud Homaniyan; Elahe Arab Ameri (رشد و یادگیری حرکتی ورزشی, 2015)
The purpose of this current study was to investigate the influence of perceptual-motor trainings on motor skills of girls with trainable mental retardation. so 20 girls with trainable mental retardation in the town of Marivan welfare organization with the average of 8/3 ±1/11 years and IQ of 39/14±6/84 with purposive sampling method were studied. All girls were pretested. Then samples based on sampling method divided into two 10 groups and considered as the control and experimental groups purposefully .In this research, for assessing the gross and fine motor skills we used sections of Bruininks _ oseretsky test . The experimental group did the perceptual-motor training for 24 sessions of practice, in a week .After 24 sessions of practice both groups were post‒test .In order to study the research hypothesis, nonparametric Wilcoxon and U Mann Whithney test were used. The results of the statistical tests showed significant difference on gross motor skills in training groups (p<0.05). while the impact of this training course on gross skills was not significant statistically. The findings showed that training program used in this current research is to improve the gross motor skills in girls with trainable mental retardation and can be useful